Are pharmaceutical ads affording consumers a greater say in their health care? The evaluation and self-empowerment effects of different ad appeals in Brazil. Issue 6 (2nd November 2017) - Koinig, Isabell; Diehl, Sandra; Mueller, Barbara
ABSTRACT: Given the pharmaceutical industry's immense global importance, drug manufacturers are currently spending approximately one third of sales revenues on marketing their products. A neglected area of inquiry is pharmaceutical marketing's contribution to consumer empowerment. The present investigation proposes an Advertising-Empowerment-Model which was tested in Brazil, the most important pharmaceutical drug market in Latin America. The model includes ad-, product- and health-related variables. Based on survey data from 241 Brazilian subjects (non-student sample), the model received support for four different ad appeals (informative, emotional, mixed and CSR). Results indicate that the mixed appeal ad led to the highest degree of empowerment in all three empowerment categories ( message empowerment, self-medication empowerment, and health empowerment ) and was followed by the informative and emotional ad appeals. The CSR appeal obtained the overall lowest scores. Implications regarding the relevance of empowerment in international advertising are discussed. Additionally, limitations and directions for further research are addressed.